Professional further education of librarians in the regional space - T. A. Kapustina; N. A. Turanina (Библиосфера, 2017)
The successful implementation of tasks facing libraries requires constant improvement of library professionals’ skills. Therefore, the most important directions of library activities is concerning about the library staff professional growth. The article indicates a high interest of researchers to training and retraining library staff according to reference analysis; contains theses on current status and tendencies of developing the additional professional education regional system of librarians in frames of monitoring specialists professional preferences of Belgorod libraries; shows the most effective and successful examples of implementing innovative forms of education; elaborates priorities of the modern system of additional professional development of library professionals.